All-inorganic cesium lead iodide perovskite solar cells with stabilized efficiency beyond 15%. Issue 1 (December 2018) - Wang, Kang; Jin, Zhiwen; Liang, Lei; Bian, Hui; Bai, Dongliang; Wang, Haoran; Zhang, Jingru; Wang, Qian; Shengzhong, Liu
Abstract As the black cesium lead iodide (CsPbI3 ) tends to transit into a yellow δ-phase at ambient, it is imperative to develop a stabilized black phase for photovoltaic applications. Herein, we report a distorted black CsPbI3 film by exploiting the synergistic effect of hydroiodic acid (HI) and phenylethylammonium iodide (PEAI) additives. It is found that the HI induces formation of hydrogen lead iodide (HPbI3+x ), an intermediate to the distorted black phase with appropriate band gap of 1.69 eV; while PEAI provides nucleation for optimized crystallization. More importantly, it stabilizes the distorted black phase by hindering phase transition via its steric effects. Upon optimization, we have attained solar cell efficiency as high as 15.07%. Specifically, the bare cell without any encapsulation shows negligible efficiency loss after 300 h of light soaking. The device keeps 92% of its initial cell efficiency after being stored for 2 months under ambient conditions. Black phase cesium lead iodide perovskite is regarded as a promising candidate for solar cells, but it easily transits to undesired yellow phase. Herein, Wang et al. stabilized the black phase using molecular additives to achieve device efficiency beyond 15% with high light soaking stability.